Sacral neuromodulation for faecal incontinence - 10 years experience and long-term outcomes of a specialized centre - Šlauf, P; Vobořil, R (Rozhledy v chirurgii, 2021)
INTRODUCTION: Sacral neuromodulation/sacral nerve stimulation (SNM/SNS) has become the most successful method for treatment of faecal incontinence (FI) in the last 10 years. The high efficiency of SNM is based on the electrical stimulation of the external anal sphincter and moreover the mechanism of action of SNS can be explained by the modulation of somatovisceral reflexes and perceptions of afferent information. Therefore the mechanism of action is more complex in contrast to other methods of treatment. In the Czech Republic, the SNM was implemented for the first time in 2010 with the financial support of the IGA grant of the Ministry of Health of the Czech Republic. Since 2018, two specialized centres for the treatment of FI using the SNM method have been established in the Czech Republic. METHODS: In the years 20102020, 35 patients were indicated for SNM. The ratio of women to men was 34:1. The mean age at implantation was 62 years (range 4675). Most patients were in the 6th and 7th decade. Two diagnostic procedures were performed in all patients, percutaneous evaluation of the S2S4 sacral nerves, implantation of the Medtronic 3889 28cm stimulation tined lead electrode and its connection to an external stimulator and subsequent subchronic stimulation for 24 weeks. The criteria for permanent neurostimulator implantation were a minimum 50% reduction in the number of FI episodes per week or a 50% reduction in incontinence score. Patients were then implanted with a Medtronic InterStim II 3058 permanent neurostimulator. RESULTS: A permanent neurostimulator was implanted in 33 of 35 patients (94%). No patient died. The complication rate was 11.4%. In 2 patients it was an infectious complication. In one patient malposition of the stimulator occurred after falling down and in one patient we observed lead breakage with subsequent malfunction of the stimulator after falling down. All complications were successfully resolved by reoperation. The longterm effect of SNM was evaluated in the group of the first 15 implanted patients from 20102011. Of these, 9 patients were available, in whom a new neurostimulator was reimplanted due to loss of battery power in 20182020. The mean length of follow-up was 112 months (99124). The mean number of FI episodes per week was 1.9 (013) after neurostimulator implantation compared to 13.6 (325) before implantation. The Cleveland Clinic Incontinence Score (CCIS) was 8.3 (316) after neurostimulator implantation compared to CCIS 18.8 (1520) before implantation. Both FI episode counts and CCIS scores were significantly lower (p.
Keywords: Lumbosacral Plexus; kvalita života; faecal incontinence; Male; Female; Sacrum; long-term results; Treatment Outcome; elektrostimulační terapie; anální kanál; plexus lumbosacralis; mužské pohlaví; ženské pohlaví; fecal incontinence; long-term outcomes; Quality of Life; Electric Stimulation Therapy; sacral neuromodulation; fekální inkontinence; křížová kost; Anal Canal; výsledek terapie; lidé; Fecal Incontinence; Humans; sacral nerve stimulation